Integrated analysis of potential microbial consortia, soil nutritional status, and agro-climatic datasets to modulate P nutrient uptake and yield effectiveness of wheat under climate change resilience - Yahya, Mahreen; Rasul, Maria; Hussain, Sayed Zajif; Dilawar, Adil; Ullah, Midrar; Rajput, Lubna; Afzal, Aftab; Asif, Muhammad; Wubet, Tesfaye; Yasmin, Sumera (Frontiers in Plant Science, 2023)
Climate change has devastating effect on wheat production thereof crop production might decline by 2030. Phosphorous-nutrient deficiency is another main limiting factor of reduced yield. Hence, there is a dire need to consider the wheat yield judiciously so the human requirements and nutrition balance can be sustained efficiently. Despite the great significance of biostimulants in sustainable agriculture, there is still lack of integrated technology encompassing the successful competitiveness of inoculated phosphate solubilizing bacteria (PSB) in agriculture system in context to climatic conditions/meteorological factors and soil nutritional status. Therefore, present study reveals the modulation of integrated P-nutrient management approach to develop potential PSB consortia for recommended wheat varieties by considering respective soil health and agro-climatic conditions. The designed consortia were found to maintain adequate viability for up to nine months, verified through field emission scanning electron microscopy and viable count. Furthermore, a significant increase in grain yield (5-8%) and seed P (4%) content was observed in consortia-inoculated wheat plants with 20% reduced DAP application under net house conditions. Fluorescent in situ hybridization analysis of roots and amplification of gcd gene of Ochrobactrum sp. SSR indicated the survival and rhizosphere-competency of inoculated PSB. Categorical principal component analysis (CAT-PCA) showed a positive correlation of inoculated field-grown wheat varieties in native soils to grain yield, soil P content and precipitation for sites belong to irrigated plains while seed P content, soil organic matter and number of tillers for site belong to dry mountains. However, the impact of inoculation at sites belong to the Indus delta was found significantly correlated to soil K content, EC and temperature. Additionally, significant increase in grain yield (15 %) and seed P (14%) content was observed in inoculated wheat plants. Thus, the present study demonstrates for the first time the need to integrate soil biological health and ago-climatic conditions for consistent performance of augmented PSB and enhanced P nutrient-uptake to curtail soil pollution caused by extensive use of agrochemicals. This study provides innovative insights and identifies key questions for future research on PSB to promote its successful implementation in agriculture.